Comparative analysis of the production-average consumption proportion of the main fruits in Romania and the European Union - Daniela Nicoleta Bădan; Petruța Antoneta Turek-Rahoveanu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Taking under consideration the importance of fruits in human food, this article aims to follow the evolution of surfaces, productions, annual average fruit consumption, the import and export in Romania compared to the E.U. with the purpose of evaluating the sector as well as their necessity in human food. The increasing predisposition of the annual average consumption starting 2011 is due to the people's orientation towards a healthy food based on fresh fruits and vegetables, which makes one of the elements necessary for a balanced life. Human consumption represented the main destination of the inland consumption (97%) in 2014/2015 as well as in the previous years. The import value has reached a maximum level of 2,14 times (2016) compared to reference year (2010). The fruit imports increase year by year, exceeding exports, because the fruit productions in the last years have been of low quality which is why they have been sent to the food industry in order to be processed.
Keywords: Q13; L11; 330; average consumption; import value; export value